2013
DOI: 10.1155/2013/149640
|View full text |Cite
|
Sign up to set email alerts
|

Providers' Perceptions of Challenges in Obstetrical Care for Somali Women

Abstract: Background. This pilot study explored health care providers' perceptions of barriers to providing health care services to Somali refugee women. The specific aim was to obtain information about providers' experiences, training, practices and attitudes surrounding the prenatal care, delivery, and management of women with Female Genital Cutting (FGC). Methods. Individual semi-structured interviews were conducted with 14 obstetricians/gynecologists and nurse midwives in Columbus, Ohio. Results. While providers did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 36 publications
4
105
0
Order By: Relevance
“…A study of 243 American certified nurse midwives by Hess et al (2010) revealed that they had better technical knowledge on FGM types and complication than knowledge of cultural and legal issues. A lack of cultural knowledge was also reported by midwives in another US study by Lazar et al (2013).…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…A study of 243 American certified nurse midwives by Hess et al (2010) revealed that they had better technical knowledge on FGM types and complication than knowledge of cultural and legal issues. A lack of cultural knowledge was also reported by midwives in another US study by Lazar et al (2013).…”
Section: Resultsmentioning
confidence: 62%
“…Of the 10 papers included in the review, there were four that employed qualitative methods (Berggren et al, 2004;Isman et al, 2013;Lazar et al, 2013;Leval et al, 2004), five used a quantitative survey design (Jacoby & Smith, 2013;Korfker et al, 2012;Tamaddon et al, 2006;Widmark et al, 2002;Zaidi et al, 2007) and one used a survey design that also collected qualitative data. Eight papers were from HIC and two provided data about midwives in LMIC (Berggren, et al, 2004;Isman, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations